Beyond Neuronal Heat Sensing: Diversity of TRPV1 Heat-Capsaicin Receptor-Channel Functions - Shuba, Yaroslav M. (Frontiers in Cellular Neuroscience, 2021)
Transient receptor potential vanilloid 1 (TRPV1) is a calcium-permeable ion channel best known for its ability to be gated by the pungent constituent of red chili pepper, capsaicin, and related chemicals from the group of vanilloids as well as by noxious heat. As such, it is mostly expressed in sensory neurons to act as a detector of painful stimuli produced by pungent chemicals and high temperatures. Its activation is also sensitized by the numerous endogenous inflammatory mediators and second messengers, making it an important determinant of nociceptive signaling. Except for such signaling, though, neuronal TRPV1 activation may influence various organ functions by promoting the release of bioactive neuropeptides from sensory fiber innervation organs. However, TRPV1 is also found outside the sensory nervous system in which its activation and function is not that straightforward. Thus, TRPV1 expression is detected in skeletal muscle; in some types of smooth muscle; in epithelial and immune cells; and in adipocytes, where it can be activated by the combination of dietary vanilloids, endovanilloids, and pro-inflammatory factors while the intracellular calcium signaling that this initiates can regulate processes as diverse as muscle constriction, cell differentiation, and carcinogenesis. The purpose of the present review is to provide a clear-cut distinction between neurogenic TRPV1 effects in various tissues consequent to its activation in sensory nerve endings and non-neurogenic TRPV1 effects due to its expression in cell types other than sensory neurons.